2011
DOI: 10.2119/molmed.2010.00143
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Enzymes and Stem Cell Markers Are Upregulated during Androgen Deprivation in Prostate Cancer

Abstract: Considerable levels of testosterone and dihydrotestosterone (DHT) are found in prostate cancer (PCa) tissue after androgen deprivation therapy. Treatment of surviving cancer-initiating cells and the ability to metabolize steroids from precursors may be the keystones for the appearance of recurrent tumors. To study this hypothesis, we assessed the expression of several steroidogenic enzymes and stem cell markers in clinical PCa samples and cell cultures during androgen depletion. Gene expression profiles were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 20 publications
8
65
0
Order By: Relevance
“…1) [19,26]. These preclinical findings are consistent with clinical observations that MET expression is higher in tumor samples from patients with CRPC compared with tumor samples from patients who have not yet undergone androgen-deprivation therapy [27], underlining that upregulation of the MET signaling correlated with the emergence of resistance to androgen suppression [28,29]. A possible explanation of this difference is resulted from preclinical studies showing that in vitro the AR negatively regulates the transcription and expression of MET in a ligand-dependent manner, leading to the inhibition of cell proliferation [29].…”
Section: Met and Vegfr Signaling In Prostate Cancersupporting
confidence: 85%
“…1) [19,26]. These preclinical findings are consistent with clinical observations that MET expression is higher in tumor samples from patients with CRPC compared with tumor samples from patients who have not yet undergone androgen-deprivation therapy [27], underlining that upregulation of the MET signaling correlated with the emergence of resistance to androgen suppression [28,29]. A possible explanation of this difference is resulted from preclinical studies showing that in vitro the AR negatively regulates the transcription and expression of MET in a ligand-dependent manner, leading to the inhibition of cell proliferation [29].…”
Section: Met and Vegfr Signaling In Prostate Cancersupporting
confidence: 85%
“…It has been previously shown that the AKR1C3 enzyme of the 550 steroid pathway is up-regulated in response to castration in clinical 551 patient samples [56]. AKR1C3 mediates the pro-androgenic 552 conversion of androstanediol and androstenedione to T [30,56]. 553 We confirm that this up-regulation also occurs in the LNCaP model 554 (Fig.…”
supporting
confidence: 61%
“…Conversely, 51 hypocholesterolemia generally inhibits prostatic tumor growth 52 [21]. Serum cholesterol levels are aligned with prostate cancer 53 progression, and explanations for these effects include: age- 54 related declines in the ability of prostate tissue to regulate 55 cholesterol [27]; activation of growth factor signal transduction 56 pathways [26]; and increased availability of substrate for local 57 steroid synthesis [21]. Thus, diet regimes that deplete serum 58 cholesterol may suppress CRPC tumor progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, given their upregulation of AR and numerous enzymes involved in the metabolism of adrenal steroids following androgen deprivation, DuCaPs may represent an ideal in vitro model system to study intratumoral de novo androgen synthesis, a key mechanism underlying progression to CR-PCa ( Fig. 2; Locke et al 2008, Pfeiffer et al 2011.…”
Section: Cell Lines Established From Xenotransplanted Tumorsmentioning
confidence: 99%